2018
DOI: 10.1016/j.compedu.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Implementation fidelity in computerised assessment of book reading

Abstract: Measuring the implementation fidelity (IF) or integrity of interventions is extremely important, since without it a positive or negative outcome cannot be interpreted. However, IF is actually measured relatively rarely. Direct and indirect methods of measurement have been used in the past, but tend to over-emphasize teacher behaviour. This paper focuses on student behaviour collated through computers -an interesting alternative. It deals with the reading of real books and reading achievement, for which variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…However, our results do not indicate such hypothesized association between the time students spent on reading story and feedback pages and the digital learning outcomes. In literature, consensus has not yet been reached about the associations between reading time and reading outcomes (Goldhammer et al, 2014;Topping, 2018). Our findings add one more piece of evidence to the argument that there is no direct correlation between the time reading the e-book pages with students' learning and reading outcomes.…”
Section: Non-significant Findings For the Time And Frequency-related Log Variablesmentioning
confidence: 56%
See 1 more Smart Citation
“…However, our results do not indicate such hypothesized association between the time students spent on reading story and feedback pages and the digital learning outcomes. In literature, consensus has not yet been reached about the associations between reading time and reading outcomes (Goldhammer et al, 2014;Topping, 2018). Our findings add one more piece of evidence to the argument that there is no direct correlation between the time reading the e-book pages with students' learning and reading outcomes.…”
Section: Non-significant Findings For the Time And Frequency-related Log Variablesmentioning
confidence: 56%
“…Similarly, Goldhammer et al (2014) examined the associations between time spent reading digital text and reading competency and found that students who had weaker reading skills tended to spend more time reading the text. However, Topping (2018) had contradictory findings such that students who spent longer time in text reading tended to have better reading comprehension outcomes.…”
Section: Stealth Assessment and In-system Indicatorsmentioning
confidence: 99%
“…This central scoring enables the collection of large samples of data. The present paper is a companion to previous papers focused on reading (Topping, 2017(Topping, , 2018.…”
Section: The Current Papermentioning
confidence: 95%